Rigid Patient Positioning is Unreliable in Total Hip Arthroplasty. - Milone, Michael T.; Schwarzkopf, Ran; Meere, Patrick A.; Carroll, Kaitlin M.; Jerabek, Seth A.; Vigdorchik, Jonathan (Journal of Arthroplasty, 2017)
Background: To our knowledge, no study has assessed the ability of rigid patient positioning devices to afford arthroplasty surgeons with ideal acetabular orientation throughout surgery. The purpose of this study is to use robotic arm-assisted computer navigation to assess the reliability of pelvic position in total hip arthroplasty performed on patients positioned with rigid positioning devices.Methods: A prospective cohort of 100 hips (94 patients) underwent robotic-guided total hip arthroplasty in the lateral decubitus position from the posterior approach, 77 stabilized by universal lateral positioner, and 23 by peg board. Before reaming, computed tomography-templated computer software generated true values of pelvic anteversion and inclination based on the position of the robot arm registered to the patient's preoperative pelvic computed tomography.Results: Mean alteration in anteversion and inclination values was 1.7° (absolute value, 5.3°; range, -20° to 20°) and 1.6° (absolute value, 2.6°; range, -8° to 10°), respectively. And 22% of anteversion values were altered by >10° and 41% by >5°. There was no difference between hip positioners used (P = .36). Anteversion variability was correlated with body mass index (P = .02).Conclusion: Despite the use of rigid patient positioning devices-a lateral hip positioner or peg board-this study reveals clinically important malposition of the pelvis in many cases, especially with regard to anteversion. These results show a clear need to pay particular attention to anatomic landmarks or computer-assisted techniques to assure accurate acetabular cup positioning. Patient positioning should not be solely trusted.